Model-Model Manajemen Bimbingan dan Konseling dalam Pendidikan Modern: Sebuah Tinjauan Literatur (International Forum of Researchers and Lecturers, 2025)
This article examines various guidance and counseling (BK) management models relevant to the context of modern education in Indonesia. The models discussed include POAC (Planning, Organizing, Actuating, Controlling) management, comprehensive BK services, school-based BK management, specialized service management, and the use of digitalization in BK services. This review was compiled using a literature review method, drawing on various credible national sources, such as scientific journals, reference books, and education policy documents. The purpose of this research is to provide an in-depth understanding of the characteristics, principles, and implementation of each BK management model in educational practice. The results indicate that each model has its own advantages and limitations, both in terms of service planning, resource management, and the effectiveness of service delivery to students. Therefore, the selection and implementation of a BK management model must be tailored to the needs of the school, the availability of professional staff, infrastructure, and student characteristics. The integration of a systematic, data-driven, and adaptive management approach to developments in information technology is a key factor in improving the quality and effectiveness of BK services. This article is expected to provide theoretical and practical contributions to school counselors, educators, and education policymakers.